Effectiveness of Mindfulness-Based Relapse Prevention Program as an Adjunct to the Standard Treatment for Smoking: A Pragmatic Design Pilot Study. Issue 9 (28th March 2020) - Weiss de Souza, Isabel Cristina; Kozasa, Elisa Harumi; Bowen, Sarah; Richter, Kimber P; Sartes, Laisa Marcorela Andreoli; Colugnati, Fernando Antônio Basile; Noto, Ana Regina
Abstract: Introduction: Posttreatment relapse is a major roadblock to stemming the global epidemic of tobacco-related illness. This article presents results from a pilot trial evaluating the feasibility and initial efficacy of Mindfulness-Based Relapse Prevention (MBRP) as an adjunct to standard relapse prevention treatment (ST) for smoking cessation. Aims and Methods: Smokers ( n = 86) in the maintenance phase of treatment were randomized to receive either ST plus MBRP (MBRP) ( n = 44) or ST alone (ST) ( n = 42). Data were collected at baseline and at 4-, 12-, and 24-week follow-up points. We evaluated the feasibility of the protocol with frequency analysis, and the efficacy with both intention to treat and complete case analyses of the effects of MBRP on abstinence. Secondary outcomes included mindfulness, craving, depression, anxiety, and positive/negative affect. Results: High adherence suggested MBRP is acceptable and feasible. Participants in the MBRP group reported increases in mindfulness ( M = −7.833, p = .016), and reductions in craving ( M = 17.583, p = .01) compared with the ST group. Intention to treat analysis found that, compared with MBRP (36.4%), ST (57.1%) showed trend-level superiority in abstinence at Week 4 (Prevalence Ratio = 0.63, p = .06); however at Week 24, the ST group (14.3%) demonstrated a twofold greater decrease in abstinence, compared with the MBRP group (20.1%) (Prevalence Ratio = 2.25, p = .08). Therefore, the MBRP group maintained a higher abstinence rate for longer. Reported effects were greater in the complete case analysis. Conclusions: MBRP holds promise for preventing relapse after aided tobacco quit attempts. Implications: Findings suggest that MBRP is acceptable, feasible, and valued by participants. At 24-week follow-up, there was a large effect size and a statistical trend toward fewer MBRP patients relapsing compared with ST patients. MBRP conferred ancillary benefits including reductions in craving and increases in levels of mindfulness. MBRP for tobacco cessation is highly promising and merits further research. Trial Registration: clinicaltrials.gov. Identifier: NCT02327104.